Physical activity and functional preservation in older adults with hip osteoarthritis: A comparative analysis of age cohorts in the SHARE study - Graziella Martins de Vasconcellos de Mello; Fernando Tadeu Trevisan Frajácomo; Ariele B. Haagsma; Dyego L. B. Souza; Vanessa Barbosa de Oliveira; Márcia Olandoski; José Rocha Faria Neto; Javier Jerez-Roig; Cristina P. Baena (PLoS ONE, 2025)
Background Hip osteoarthritis (HOA) is a major contributor to functional impairment in older adults. Physical inactivity and comorbidities are commonly associated with declines in functional ability. However, the relationship between physical inactivity and functional outcomes in individuals with HOA, particularly those aged 80 years and older, remains underexplored. Objective This study investigated the association between physical inactivity and functional limitations in older adults with HOA, focusing on two age groups: 60–79 years and 80–100 years. Methods We analyzed data from Wave 5 of the Survey of Health, Aging, and Retirement in Europe (SHARE), constructing univariate and multivariable logistic regression models. Functional limitations served as dependent variables, with physical inactivity as the primary explanatory variable and number of chronic conditions, body mass index (BMI), gender, education, and depression as covariates. Results The study included 2,088 participants (mean age 73.1 ± 8.5 years; 73.7% female). Physical inactivity was reported by 16.8% (n =  261) of participants aged 60–79 years (n =  1,556; 72.5% female) and 49.6% of those aged 80–100 years (n =  532; 22.5% female). Poor handgrip strength and difficulty rising from a chair were significantly more prevalent among females aged 60–79 years (p <  0.002 for both). A marked decline in both physical activity and functional ability was observed between the two age groups. Physical inactivity emerged as an independent risk factor for reduced functioning across all outcomes, with stronger associations in the 80–100 years age group. Conclusions Physical inactivity is a key predictor of functional decline in older adults with HOA, with its impact being particularly pronounced among those aged 80 years and older. These findings highlight the importance of physical activity to preserve functional abilities in this population.